Molecular aspects of cervical cancer: a pathogenesis update - Vallejo-Ruiz, Verónica; Gutiérrez-Xicotencatl, Lourdes; Medina-Contreras, Oscar; Lizano, Marcela (Frontiers in Oncology, 2024)
Cervical cancer (CC) is a significant health problem, especially in low-income countries. Functional studies on the human papillomavirus have generated essential advances in the knowledge of CC. However, many unanswered questions remain. This mini-review discusses the latest results on CC pathogenesis, HPV oncogenesis, and molecular changes identified through next-generation technologies. Interestingly, the percentage of samples with HPV genome integrations correlates with the degree of the cervical lesions, suggesting a role in the development of CC. Also, new functions have been described for the viral oncoproteins E5, E6, and E7, resulting in the acquisition and maintenance of cancer hallmarks, including proliferation, immune response evasion, apoptosis, and genomic instability. Remarkably, E5 oncoprotein affects signaling pathways involved in the expression of interferon-induced genes and EGFR-induced proliferation, while E6 and E7 oncoproteins regulate the DNA damage repair and cell cycle continuity pathways. Furthermore, next-generation technologies provide vast amounts of information, increasing our knowledge of changes in the genome, transcriptome, proteome, metabolome, and epigenome in CC. These studies have identified novel molecular traits associated with disease susceptibility, degree of progression, treatment response, and survival as potential biomarkers and therapeutic targets.